In Vitro Study of Adsorption Kinetics of Dextromethorphan Syrup onto Activated Charcoal in Simulated Gastric and Intestinal Fluids - Shobha Regmi; Balmukunda Regmi; Sajan Lal Shyaula; Shiva Pathak; Bishnu Prasad Bhattarai; Saroj Kumar Sah (Journal of Chemistry)
Adsorption kinetics of dextromethorphan (DXM) syrup in simulated gastric and intestinal fluids onto activated charcoal (AC) were investigated in an in vitro model. The adsorption studies were performed as a function of time, initial concentration, and temperature. The quantification of DXM adsorbed onto AC was obtained from the Langmuir adsorption isotherms using HPLC. The maximum adsorption capacities (at 95% confidence limits) of AC for DXM were 111.615 [106.38; 126.85] mg in simulated intestinal environment (pH 6.8) and 78.314 [86.206; 70.422] mg in simulated gastric environment (pH 1.2). The adsorption capacity of AC for DXM in simulated gastric fluid (pH 1.2) was not significantly different from the adoption capacity of AC for DXM in simulated intestinal fluid (pH 6.8). Moreover, the adsorption kinetics behavior of dextromethorphan onto AC followed pseudo-second-order kinetics. Our results show that AC in therapeutically acceptable doses can be beneficial in the majority of oral overdose of DXM.